2021
DOI: 10.1093/plcell/koab263
|View full text |Cite
|
Sign up to set email alerts
|

FYVE2, a phosphatidylinositol 3-phosphate effector, interacts with the COPII machinery to control autophagosome formation in Arabidopsis

Abstract: Autophagy is an intracellular trafficking mechanism by which cytosolic macromolecules and organelles are sequestered into autophagosomes for degradation inside the vacuole. In various eukaryotes including yeast, metazoans, and plants, the precursor of the autophagosome, termed the phagophore, nucleates in the vicinity of the endoplasmic reticulum (ER) with the participation of phosphatidylinositol 3-phosphate (PI3P) and the coat protein complex II (COPII). Here we show that Arabidopsis thaliana FYVE2, a plant-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 82 publications
4
45
0
Order By: Relevance
“…Our findings are consistent with a role in autophagosome maturation as opposed to autophagosome biogenesis as was recently suggested (Kim et al, 2022): (i) our differential centrifugation-based autophagosome enrichment procedure selects for proteins that associate with closed, mature autophagosomes. AP-MS did not identify biogenesis components but did identify trafficking related proteins such as Myosin 14 (Fig 1B, Table S3), (ii) we observe fully formed autophagosomes in micrographs obtained from cfs1 mutants indistinguishable from and in similar numbers to wild type (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are consistent with a role in autophagosome maturation as opposed to autophagosome biogenesis as was recently suggested (Kim et al, 2022): (i) our differential centrifugation-based autophagosome enrichment procedure selects for proteins that associate with closed, mature autophagosomes. AP-MS did not identify biogenesis components but did identify trafficking related proteins such as Myosin 14 (Fig 1B, Table S3), (ii) we observe fully formed autophagosomes in micrographs obtained from cfs1 mutants indistinguishable from and in similar numbers to wild type (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…1B-C). Since CFS1 has previously been linked to autophagy and FYVE and SYLF domain-containing proteins are well-known players in vesicle trafficking (Sutipatanasomboon et al, 2017; Kim et al, 2022; Melia et al, 2020), we decided to characterize CFS1 in depth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated identification of the same proteins actually added more confidence to the IP-MS study. A number of proteins identified are worthy of further study and may help answer some existing questions in plant autophagy, such as which membranes or vesicles, apart from COPII vesicles ( Zeng et al, 2021 ; Kim et al, 2022 ), may contribute to autophagosome formation. Early studies for plant autophagy had identified ATI1 and ATI2 as plant-specific ATG8-interacting proteins; both were uncovered through an Y2H screen ( Honig et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant cells contain not only canonical Atg components, but also plant‐specific proteins functioning in autophagosome formation [21–23]. Recent studies have demonstrated the contribution of COPII vesicles to the autophagy pathway in plants [24,25]. In this review, we summarize the roles of plant COPII vesicles in canonical and non‐canonical ER export and recap known facts of plant autophagy interplaying with the endomembrane system.…”
Section: Figmentioning
confidence: 99%